(untitled) (Journal of Current and Advance Medical Research, 2025)
Background: Fish farming in Lalpur Upazila under Natore District plays a vital role in local livelihoods and food security, necessitating an assessment of its current status and potential for future development. Objective: The general objective of the study was to assess the existing status and explore the future potentials of fish farming in Lalpur Upazila under Natore District of Bangladesh. Methodology: This study was designed as a descriptive survey to evaluate the current status and potential of fish farming in Lalpur Upazila under Natore District of Bangladesh. Data were collected through structured questionnaires, interviews, and field observations to ensure comprehensive coverage of farming practices and challenges. The study was conducted in various villages within Lalpur Upazila, where fish farming is actively practiced. The study period spanned from January to June 2024. A combination of purposive and random sampling techniques was used to select respondents, including fish farmers, local authorities, and fisheries officers. Collected data were analyzed using both qualitative and quantitative methods to draw meaningful conclusions. Results: Most respondents (44.0%) were aged 30 to 40 years, 36.0% had education beyond Higher Secondary Certificate, and 48.0% received formal training in fish farming. Farmers mainly cultured Indian major carps, silver carp, and common carp, while rotenone and phostoxin were used to remove unwanted species. Fertilizers like urea, TSP, SSP, mustard oil cake, and cow dung and supplementary feeds were widely used. Production ranged from 710.40 to 10,785.10 kg/ha/year, with an average yield of 3,744.98±2,530.40 kg/ha. Net profits varied from 48,127.80 to 377,157.00 Tk./ha/year. Constraints included low-quality seed, technical gaps, labor shortages, diseases, lack of credit, high input costs, theft, and water pollution. Fish production increased from 3,280 MT in 2017 to 4,750 MT in 2021. Conclusion: Based on the findings, it can be concluded that fish farming in Lalpur Upazila holds significant potential for expansion and increased productivity, provided that existing challenges are addressed through improved support, resources, and training. Journal of Current and Advance Medical Research, July 2024;11(2):97-101